2013
DOI: 10.1002/adma.201204839
|View full text |Cite
|
Sign up to set email alerts
|

Large Resistive Switching in Ferroelectric BiFeO3 Nano‐Island Based Switchable Diodes

Abstract: The demand for non-volatile memory technologies that offer high speed, high storage density and low power consumption has stimulated extensive research into new functional materials and device physics. [1][2][3][4][5] Nano-ferronic devices based on multiferroic/ferroelectric materials have been emerging as nextgeneration nano-electronics, which deal with the interplay between ferroic orders (e.g. ferroelectricity and ferromagnetism) and electronic transport on the nanoscale. [ 6 ] Recent investigations into va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
122
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(133 citation statements)
references
References 28 publications
8
122
1
1
Order By: Relevance
“…However, many recent investigations have demonstrated a dominant role played by the ferroelectric polarization in switchable diode effect [26][27][28][29]. Jiang et al confirmed that the resistive switching curves of the SRO/BFO/Pt structure have identical shapes to the Polarzation-Voltage loops.…”
Section: Recent Progress In Switchable Ferroelectric Diodesmentioning
confidence: 58%
See 3 more Smart Citations
“…However, many recent investigations have demonstrated a dominant role played by the ferroelectric polarization in switchable diode effect [26][27][28][29]. Jiang et al confirmed that the resistive switching curves of the SRO/BFO/Pt structure have identical shapes to the Polarzation-Voltage loops.…”
Section: Recent Progress In Switchable Ferroelectric Diodesmentioning
confidence: 58%
“…Since then many similar phenomena have been observed in various ferroelectric thin films [15][16][17][18][19]. Most interestingly, the switchable diode effect has been demonstrated recently in various ferroelectric structures ranging from organic films [20,21], inorganic bulks [22][23][24], and inorganic films [25][26][27][28][29]. The switchable diode effect means that the polarity of the diode can be reproducibly switched by the reversion of the applied electric field in the MFM structures, due to the polarization modulated barrier.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…It has been widely studied due to its potential use for information storage applications [2,3] and low band gap; thus, its ferroelectric [4][5][6][7], ferromagnetic [8][9][10][11] and photovoltaic [12][13][14] properties have been analyzed. The BiFeO 3 perovskite is particularly interesting because having ferroelectric and ferromagnetic properties, it can display magneto-electric coupling, that is, the capacity to control electrical polarization by application of a magnetic field and control magnetism by the application of an electric field [3,15].…”
Section: Introductionmentioning
confidence: 99%